Implementation Stem-Based Flipbook Teaching Materials to Improve Students Creative Thinking Skills - Fitri, Silvi Agnia; Retnowati, Rita; Herawati, Desti (Pedagonal : Jurnal Ilmiah Pendidikan, 2023)
This study aims to apply STEM-based teaching materials in the form of flipbooks to improve students' creative thinking skills. The method used in this study is the weak experiment method with a one group pretest posttest design. The research instrument used in the form of essay test questions and questionnaire sheets. Data analysis techniques include the assessment of creative thinking skills as measured using the N-Gain formula. The results of data analysis showed that students' creative thinking skills have increased with an N-Gain achievement of 0.42 (medium category). This indicates that STEM-based teaching materials in the form of flipbooks can improve students' creative thinking skills